Laboratory testing of muscle function in the management of neuromuscular disease. Issue 5 (May 1990) - Wiles, C M; Karni, Y; Nicklin, J
Abstract : A laboratory was set up to assess muscle weakness and physical disability in patients with peripheral neuromuscular diseases. Muscle strength was mainly measured with a hand held dynamometer and results were expressed in relationship to a "guideline" range for sex: disability was expressed in terms of ordinal data with a performance score and as interval data with simple timed tests. Of 17 patients with polymyositis on immunosuppressive medication followed for a mean of 2.9 years (range 1.1 - 4.7 years) only eight became stronger one of whom died. Assessment of weakness (the major impairment), disability, body weight, creatine kinase and the patient's subjective view of their state were essential to obtaining a clear view of progress.